O Laboratório de Ensino de Matemática (LEM): contribuições na formação inicial de professores - Valadares, Denise Cardoso (Universidade Federal do Tocantins, 2024)
The present work aimed to analyze the importance and use of the Mathematics Teaching Laboratory (LEM) in the training of teachers and games. The use of the aforementioned Laboratory provides a better learning of mathematical concepts and theorems through the use of manipulative materials, in addition to being a space for exchanging experiences between teachers and students. To carry out the research, questionnaires were applied to 08 students from the mathematics course, generating data that were submitted to a qualitative analysis. The research was based on studies by Lorenzato (2006), Fiorentini and Miorim (1990, p. 2) and Miguel and Miorim (2004) and others. Finally, the results indicated that some students did not know that LEM existed, but recognized it as a pedagogical resource, a facilitator in teaching learning and in the understanding of mathematical content. They also demand more access and better organization and expansion of the laboratory.